Study on the Combustion Process and Emissions of a Turbocharged Diesel Engine with EGR - Mei Deqing; Qian Junnan; Sun Ping; Miao Yan; Zhang Shuang; Cai Yongjun (Journal of Combustion)
A high pressure EGR system was adopted to a turbocharged inter-cooled diesel engine, to analyze its combustion and emission characteristics under the condition of different loads and constant speed. Under the same steady operating mode, with the increase of EGR rate, the temperature of compressed gas ascended, the ignition delay was shortened, the pressure and temperature of the burned gas descended, and the combustion process was prolonged. According to the experimental data, it was found that, at the same EGR rate, lower the load of engine was, lower the temperature in cylinder, and higher the increase rate of CO was. However, the increase rate of HC present a falling trend. The decrease rate of the specific emission of NOx linearly varied with EGR rate with a slope of 1.651. The increase rate of smoke opacity behaved a second-order polynomial uprising trend, and the higher the load was, the sharpener the smoke opacity deteriorated, with the increase of EGR rate. From the point of emission view, the engine with EGR system can achieve the lesser exhaust emissions in some operations by adjusting the engine parameters.